Pengelolaan Limbah Sampah Rumah Tangga Sebagai Upaya Pelestarian Lingkungan Hidup - Dwi Kurniawati; Fachriyatul Kholidah; Ratu Girindra Marhaeni Negarawati; Velistya Devina Febriyanti; Denny Oktavina Radianto (Fakultas Teknik Universitas Cenderawasih, 2024)
Background: Household waste management is an important effort in preserving the environment. Household waste, which includes various types of materials such as organic and inorganic waste, has the potential to pollute the environment if not managed properly. The purpose of this writing is to provide a better understanding of the importance of managing household waste in environmental conservation efforts.Method: The research method used is a literature review which involves collecting and analyzing various sources of information relevant to the topic of household waste management. Results: Household waste management is very important to maintain environmental cleanliness and public health. Household waste, which includes organic, inorganic and hazardous waste such as batteries, can pollute the environment if not managed properly. Management methods such as waste separation, recycling and composting can help reduce the negative impact. Despite facing challenges such as minimal public awareness and limited resources, collaboration between the government, community and the private sector can improve household waste management. With good management, apart from protecting the environment and health, it can also provide economic benefits, such as additional income from recycling. Therefore, awareness of the importance of good and sustainable waste management needs to be increased.